The Role Of Environmental Performance And Capital Structure In Enhancing Firm Value: Financial Performance As A Mediating Variable In Indonesian Manufacturing Companies - Hafidz Hening Waskito; Halliya Citrasari (Universitas 17 Agustus 1945 Semarang, 2026)
This research aims to analyze the impact of environmental performance and capital structure on firm value, with financial performance as a mediating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The integration of Environmental, Social, and Governance (ESG) aspects in business strategy has become a critical issue amid regulatory pressures and stakeholder expectations for sustainable business practices. Nevertheless, the debate regarding the relationship between environmental investments and economic value creation remains ongoing, particularly in the context of capital markets in emerging markets. This research adopts a quantitative approach with a causal design. The sample consists of 50 manufacturing companies with the Corporate Environmental Performance Rating Program (PROPER) rating for 2023, selected through purposive sampling. Secondary data were collected from audited financial statements, annual reports, and official regulatory websites. Variables were measured using PROPER scores for environmental performance, Debt-to-Equity Ratio (DER) for capital structure, Return on Assets (ROA) for financial performance, and Price-to-Book Value (PBV) for firm value. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 software.